Implementation of Simple Low Cost PV Panel Characterization Kit using Arduino - et. al., R. Ramaprabha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Temperature, solar irradiation, direction and spectrum of sunlight always has influence on the generation of power in photovoltaic (PV) system. Temperature and irradiation are erratic in nature. It affects the efficiency of PV module. In view of module’s low efficiency, it is prudent to work the module at peak power point. By that maximum power can be delivered to the load under waffling temperatures and solar radiations. The PV panel characteristics are known under the standard test conditions (STC). In practical situations, the PV characteristics are undisclosed out of STC. Therefore, the measurement of PV peculiarities such as voltage, current and power are required in real-time. This paper adducing a low cost PV characterization kit which is based on Arduino UNO and Excel. It is used to monitor the characteristics on PV side as well as load which is connected to source through maximum power point tracker. A simulation study of the MPPT with perturb and observe algorithm is carried out in MatLab/Simulink. Hardware is built to validate the simulation results